2016
DOI: 10.1111/exd.12907
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfumarate effectively inhibits lymphangiogenesis via p21 induction and G1 cell cycle arrest

Abstract: Different pathologies, such as lymphoedema, cancer or psoriasis, are associated with abnormal lymphatic vessel formation. Therefore, influencing lymphangiogenesis is an interesting target. Recent evidence suggests that dimethylfumarate (DMF), an antipsoriatic agent, might have antitumorigenic and antilymphangiogenic properties. To prove this assumption, we performed proliferation and functional assays with primary human dermal lymphendothelial cells (DLEC). We could demonstrated that DMF suppresses DLEC prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The progression of the cell cycle is regulated by a number of negative regulators termed CDK inhibitors, including p21 Cip1 and p27 Kip1 (27). p21 Cip1 is a universal cell cycle inhibitor that binds to cyclin-CDK complexes and proliferating cell nuclear antigen, thereby inducing cell cycle arrest at the G1 phase (28). In addition, the upregulation of p21 Cip1 and p27 Kip1 enhances the formation of complexes with G1-S CDKs and cyclins, thereby, inhibiting their activities (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The progression of the cell cycle is regulated by a number of negative regulators termed CDK inhibitors, including p21 Cip1 and p27 Kip1 (27). p21 Cip1 is a universal cell cycle inhibitor that binds to cyclin-CDK complexes and proliferating cell nuclear antigen, thereby inducing cell cycle arrest at the G1 phase (28). In addition, the upregulation of p21 Cip1 and p27 Kip1 enhances the formation of complexes with G1-S CDKs and cyclins, thereby, inhibiting their activities (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could be demonstrated that MMF is a metabolite of DMF enhanced CD56 + natural killer cell lysis of tumor cells by degranulation and upregulation of NKp46 and CD107a [9]. In addition, our group could demonstrate that DMF effectively inhibits angiogenesis and lymphangiogenesis in part by downregulation of a vascular endothelial growth factor receptor (VEGFR)-2 [10,11]. All of these results illustrate that DMF seems to have potential antitumorigenic effects.…”
Section: Introductionmentioning
confidence: 95%
“…Various authors demonstrated that DMF suppresses the activation as well as the nuclear translocation of Nuclear factor kappa B (NfkB) and therefore characterize p65 as a central target of DMF [12,13,14]. In addition, p21 and the cell cycle seem to be important targets of DMF [4,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Because PCNA needs to be ubiquitinated for performing its biological function, these up-regulations of PCNA could not be certainly related to its promoted functions. On the other hand, p21 induces cell cycle arrest at G 1 42 and G 2 M 43 phases by inhibiting the activity of CDKs such as CDK6, CDK2 and cdc2 42 , 44 . In this study, we found that the expressions of cyclin B 3 /cdc2 and cyclin D 1 /CDK6 complexs were decreased in the AFB 1 group during the experiment.…”
Section: Discussionmentioning
confidence: 99%